Metodologías para la gestión y el manejo de resíduos en obras de infraestructura en la empresa EDICA Ltda. - Vindas-Arce, Esteban (Instituto Tecnológico de Costa Rica, 2007)
This project was created because the company EDICA Ltda. had the necessity to establish guidelines and documentation in order to incorporate new environmental policies within the constructive processes. "Overall Plan for Construction Waste Management, as it is called, was developed in order to generate a simple and functional document in the field. With this tool, not only people in charge of the project, but also those involved in the constructive process may know and have information for the handling and disposal of waste generated within the construction activities. It was also developed the Construction and Offices Waste Management Manual and other environmental practices. " With this book, people responsible for the execution of works will manage information to plan and implement methodologies regarding the waste management produced within the construction site, project offices and headquarters. Both documents are the result of the ISO 14001 analysis and national legislation, aimed at waste management and environmental practices, as well as some bibliographic research and consultation to various professionals.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2007.
Keywords: Norma; Políticas ambientales; Plan de manejo; Planificación; Sustancias peligrosas